The Influence of Marketing Mix on Airline Ticket Purchasing Decisions During the Covid-19 Pandemic in 2021 (Title.com Case Study) - Rahmat Kusnedi; Nexen Pinontoan; Sundring Djati (Jurnal Mantik, 2024)
The use of e-commerce at this time is increasing, one of which is e-commerce that provides the needs for tourism activities. Tiket.com is an e-commerce platform that has an application form in order to meet consumer needs, especially online airline tickets. Consumers in making decisions to purchase airline tickets online need factors that influence these purchases, especially with the emergence of the Covid-19 pandemic. This factor is included in the marketing mix which consists of product dimensions, price, promotion, and purchasing channels. This study was conducted to determine the effect of Tiket.com's marketing mix (X) on application users who are domiciled in DKI Jakarta on purchasing decisions (Y) of airplane tickets during the Covid-19 pandemic in 2021. The research method used is quantitative with verification types and descriptions. survey. The sampling technique was carried out using a non-probability sampling method with a purposive sampling technique and 118 respondents were used. The data analysis test was carried out by simple linear regression. The results showed that the marketing mix had an influence on purchasing decisions of 46.2% from the coefficient of determination test R2. The marketing mix is proven to have an effect on purchasing decisions with the results of the t count exceeding the t table, 9.976 > 1.980.